Women in clothes - Heti, Sheila, 1976-; Julavits, Heidi; Shapton, Leanne (Blue Rider Press, a member of Penguin Group (USA), 2014)
"An exploration of the questions we ask ourselves while getting dressed every day, and the answers from more than six hundred women"--From back cover.